Social Structures and the Ontology of Social Groups. - Ritchie, Katherine (Philosophy & Phenomenological Research, 2020)
Social groups—like teams, committees, gender groups, and racial groups—play a central role in our lives and in philosophical inquiry. Here I develop and motivate a structuralist ontology of social groups centered on social structures (i.e., networks of relations that are constitutively dependent on social factors). The view delivers a picture that encompasses a diverse range of social groups, while maintaining important metaphysical and normative distinctions between groups of different kinds. It also meets the constraint that not every arbitrary collection of people is a social group. In addition, the framework provides resources for developing a broader structuralist view in social ontology.